Building Rome in a Day. - Agarwal, Sameer; Furukawa, Yasutaka; Simon, Ian; Szeliski, Richard; Seitz, Steven M.; Curless, Brian; Snavely, Noah (Communications of the ACM, 2011)
We present a system that can reconstruct 3D geometry from large, unorganized collections of photographs such as those found by searching for a given city (e.g., Rome) on Internet photo-sharing sites. Our system is built on a set of new, distributed computer vision algorithms for image matching and 3D reconstruction, designed to maximize parallelism at each stage of the pipeline and to scale gracefully with both the size of the problem and the amount of available computation. Our experimental results demonstrate that it is now possible to reconstruct city-scale image collections with more than a hundred thousand images in less than a day.